Efek Pemberian Daun Sirsak (Annona Muricata L.) Sebagai Insektisida Botani Terhadap Mortalitas Sitophilus oryzae - Debby Moniharapon; Maria Nindatu; Faustinus Sarbunan (Faculty of Agriculture, Pattimura University, 2015)
The use of pesticides botanists to be the solution due to the use of chemical pesticides in controlling pests unwise caused negative impact on the environment. This study aims to determine the effectiveness of the leaves of the Annona muricata on mortality of Sitophilus oryzae. Research conducted at the Laboratory of Taxonomy Department of Biology, Faculty of Mathematics and Natural Sciences Ambon. The treatments tested was the heavy leaves of the soursop, consists of five levels, namely 0 g, 20 g, 25 g, 30 g and 35 g, using a completely randomized design with four replications. The results showed that showed that the treatment leaves of the Annona muricata which is effective against Sitophilus oryzae mortality was 35 g with a mortality rate reached 78.31%.